2008
DOI: 10.1021/jp803021n
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Direct Synthesis of H2O2 on Pd and Pd/Au Surfaces

Abstract: The direct synthesis of hydrogen peroxide on Pd and Pd/Au catalysts was investigated with first-principle DFT methods for periodic two-dimensional surfaces. A two-step reaction mechanism was proposed starting from a superoxo precursor state of the dioxygen molecule on Pd surface and its subsequent reaction with two hydrogen atoms situated over neighboring 3-fold positions. A competitive reaction of dioxygen dissociation leading to the nonselective formation of water was found. We have shown that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
110
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 27 publications
10
110
0
Order By: Relevance
“…For free formic acid in gas phase, the calculated bond lengths are 1.106 (1.097) Å for C-H, 1.357 (1.343) Å for C-O1, 1.218 (1.202) Å for C-O2 and 0.986 (0.972) Å for O1-H, our results are in agreement with previous experimental values [21] displayed in the parentheses. Formic acid has two adsorption modes, ''on top'' and ''bridge'' (shown in Fig.…”
Section: Formic Acidsupporting
confidence: 92%
“…For free formic acid in gas phase, the calculated bond lengths are 1.106 (1.097) Å for C-H, 1.357 (1.343) Å for C-O1, 1.218 (1.202) Å for C-O2 and 0.986 (0.972) Å for O1-H, our results are in agreement with previous experimental values [21] displayed in the parentheses. Formic acid has two adsorption modes, ''on top'' and ''bridge'' (shown in Fig.…”
Section: Formic Acidsupporting
confidence: 92%
“…Ham et al [30] suggested by theoretical studies that Pd monomers surrounded by less active Au atoms suppress O-O bond scission and allow enhancing the selectivity to H 2 O 2 . Staykov et al [34] also by theoretical approach indicated that the presence of surface gold atoms blocks this dissociation of chemisorbed oxygen and increases the selectivity toward H 2 O 2 .…”
Section: Introductionmentioning
confidence: 97%
“…The exposed facet is one of major factors to determine catalytic properties of Au or AuPd particles. There are several theoretical studies [20,[25][26][27][28][29][30][31][32] of H 2 O 2 synthesis on low index Pd, Au, Pt surfaces or small Au clusters. However, a systematically comparative study of the key elementary reactions for H 2 O 2 and H 2 O formation on these low index Au surfaces, especially Au(111), Au(100) and Au(110) and stepped Au surfaces, is very necessary.…”
Section: Introductionmentioning
confidence: 99%